2013
DOI: 10.3109/13880209.2013.803208
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects ofEryngium kotschyiandEryngium maritimumon Hep2, HepG2, Vero and U138 MG cell lines

Abstract: Context: Eryngium maritimum L. and the endemic Eryngium kotschyi Boiss. of the Apiaceae family are used for antiinflammatory, antivenom, antinociceptive and diuretic purposes in folk medicine in Turkey.Objective: This study investigated the cytotoxic effects of the plant extracts belonging to Eryngium L. genus on various cell lines. Materials and methods: Cytotoxic activites of the lyophilized aqueous aereal and root parts of the plant extracts on human hepatocellular carcinoma (HepG2), human laryngeal epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…accordance with the US National Cancer Institute guidelines, extracts with IC 50 values below 30 μg/mL are considered potent candidates for further investigations with regards to their anticancer potential [35]. Consequently, it is of value to gauge the S. coriaceum effect on the replicative ability of the cancer cells, at doses equivalent to ½ X, X and 2X IC 50 values.…”
Section: Plos Onementioning
confidence: 99%
“…accordance with the US National Cancer Institute guidelines, extracts with IC 50 values below 30 μg/mL are considered potent candidates for further investigations with regards to their anticancer potential [35]. Consequently, it is of value to gauge the S. coriaceum effect on the replicative ability of the cancer cells, at doses equivalent to ½ X, X and 2X IC 50 values.…”
Section: Plos Onementioning
confidence: 99%
“…Eryngium maritimum is also an important halophyte, since leaves extracts exhibited strong antioxidant activity and antibacterial activity against Pseudomonas aeruginosa and Pseudomonas fluorescens (Meot-Duros, Le Floch, & Magné, 2008), while Yurdakök and Baydan (2013) reported that extracts from the aerial and root parts showed cytotoxic effects against human hepatocellular carcinoma (HepG2) and human laryngeal epidermoid carcinoma (Hep2) cells. In a recent study, Amessis-Ouchemoukh et al 2014observed that leaves extracts exhibited significant acetylcholinesterase inhibitory activity, while stems had a stronger metal chelating activity than leaves.…”
Section: Health Effectsmentioning
confidence: 99%
“…As with the baboon and rhesus macaque, genetic maps have been developed for C. a. sabaeus (Jasinska et al, 2007). The use of this cell line continues to be widespread in biomedical research Yurdakök and Baydan, 2013). Some of the many research areas include African trypanosomiasis infection (Ouwe-Missi-Oukem- Boyer et al, 2006), vaccinology (Martín et al, 2009), HIV/ AIDS (Hatziioannou and Evans, 2012), hypertension (Ervin and Palmour, 2003), neurological disease (Lemere et al, 2004;Harvey et al, 2000), psychology and social behavior (Bailey et al, 2007;Fairbanks et al, 2004), atherosclerosis and metabolic syndrome (Rayner et al, 2011;van Jaarsveld et al, 2002), and leishmania (Olobo et al, 2001).…”
Section: Research Usesmentioning
confidence: 99%